Detecting development of speaking proficiency with a group oral test: A quantitative analysis. (April 2019) - Leaper, David A.; Brawn, James R.
This paper is an investigation into the use of the group oral discussion test (GOT) to detect changes in speaking proficiency over a two-year period. In this test, three or four test-takers discuss a topic for up to 10 minutes without outside intervention. The performance of 53 Japanese university English major students on this test was videoed before their classes started and at the end of their first and second years of study. Indices of complexity, accuracy, and fluency were calculated and interactive function was analysed to create indices that tracked initiating, responding, developing, and collaborating functions. Improvements were detected in most of the indices over the three administrations, with varying patterns of development. However, the test-takers' scores in five rated scales only improved significantly in the second administration. Possible reasons for this discrepancy are discussed, as are the implications this study has for the GOT format and its administration.